1998
DOI: 10.1021/bi980931b
|View full text |Cite
|
Sign up to set email alerts
|

Pore Formation by Nisin Involves Translocation of Its C-Terminal Part across the Membrane

Abstract: Nisin is an amphiphilic peptide with a strong antimicrobial activity against various Gram-positive bacteria. Its activity results from permeabilization of bacterial membranes, causing efflux of cytoplasmic compounds. To get information on the molecular mechanism of membrane permeabilization, a mutant of nisin Z containing the C-terminal extension Asp-(His)6 was produced. The biological and anionic lipid-dependent membrane activity of this peptide was very similar to that of nisin Z. Analysis of the pH dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
0
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 28 publications
(59 reference statements)
9
64
0
1
Order By: Relevance
“…The high potency that derives from such a target-mediated poration may well explain why nisin is so much more effective against bacteria in which the docking molecule is available for binding as compared with a peptide that apparently acts in a nontargeted fashion such as magainin 2 (5). The results reported here and in previous papers on the molecular mechanisms of activity of nisin in the absence of lipid II (7,8,18,24,28,36) show that nisin can permeabilize membranes via two different mechanisms. At high concentrations (M range) pores can be formed without lipid II, i.e.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The high potency that derives from such a target-mediated poration may well explain why nisin is so much more effective against bacteria in which the docking molecule is available for binding as compared with a peptide that apparently acts in a nontargeted fashion such as magainin 2 (5). The results reported here and in previous papers on the molecular mechanisms of activity of nisin in the absence of lipid II (7,8,18,24,28,36) show that nisin can permeabilize membranes via two different mechanisms. At high concentrations (M range) pores can be formed without lipid II, i.e.…”
Section: Discussionsupporting
confidence: 73%
“…The N-terminal segment of the lantibiotic is essential for binding, and a negative surface charge is not necessary. The C-terminal part of nisin is then assumed to translocate across the membrane, in accordance with the translocation found in the absence of lipid II (28). For this step the flexible hinge region between ring clusters A, B, C and D, E is important.…”
Section: Figmentioning
confidence: 71%
See 1 more Smart Citation
“…Most type A lantibiotics are cationic, which appears to enhance their interaction with the negatively charged lipid membrane of the target organism. However, introducing more positively charged amino acids into the C-terminus of nisin did not lead to enhanced antimicrobial activity [30,32,33] and might even hinder pore formation [34]. Analogously, we found that adding more C-terminal lysines did not further increase antimicrobial activity of nisin- (1-22).…”
Section: Positive C-terminal Charge Enhances Antimicrobial Activity Omentioning
confidence: 61%
“…Interestingly, [D]-K 3 H 3 L 9 has no pH-dependent activity, although it contains a significant number of histidines. This differs from several natural antimicrobial peptides that have pH-dependent activity, although they contain only a few histidines in their sequence (36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47).…”
Section: Discussionmentioning
confidence: 93%